Bis(N-amidinohydrazones) and N-(amidino)-N′-aryl-bishydrazones: New classes of antibacterial/antifungal agents. Issue 1 (1st January 2017) - Shrestha, Sanjib K.; Kril, Liliia M.; Green, Keith D.; Kwiatkowski, Stefan; Sviripa, Vitaliy M.; Nickell, Justin R.; Dwoskin, Linda P.; Watt, David S.; Garneau-Tsodikova, Sylvie
Graphical abstract: Abstract: The emergence of multidrug-resistant bacterial and fungal strains poses a threat to human health that requires the design and synthesis of new classes of antimicrobial agents. We evaluated bis( N -amidinohydrazones) and N -(amidino)- N′ -aryl-bishydrazones for their antibacterial and antifungal activities against panels of Gram-positive/Gram-negative bacteria as well as fungi. We investigated their potential to develop resistance against both bacteria and fungi by a multi-step resistance-selection method, explored their potential to induce the production of reactive oxygen species, and assessed their toxicity. In summary, we found that these compounds exhibited broad-spectrum antibacterial and antifungal activities against most of the tested strains with minimum inhibitory concentration (MIC) values ranging from <0.5 to >500 μM against bacteria and 1.0 to >31.3 μg/mL against fungi; and in most cases, they exhibited either superior or similar antimicrobial activity compared to those of the standard drugs used in the clinic. We also observed minimal emergence of drug resistance to these newly synthesized compounds by bacteria and fungi even after 15 passages, and we found weak to moderate inhibition of the human Ether-à-go-go -related gene (hERG) channel with acceptable IC50 values ranging from 1.12 to 3.29 μM. Overall, these studies show that bis( N -amidinohydrazones) and N -(amidino)- N ′-aryl-bishydrazones are potentially promising scaffolds for the discovery of novel antibacterial and antifungal agents.